Greek Issue in British Foreign Policy (1914-1917) - Hrachov, А. (Міжнародні зв’язки України: наукові пошуки і знахідки, 2020)
The article sheds light on British policy of bringing Greece into the First
World War on Entente’s side. Interests of mutual cooperation between Greek
political circles and Foreign Office, the course of negotiations about terms of
Greek participation in the war, and requirements of the sides are analyzed.
Factors that made an influence on Great Britain’s diplomacy are researched,
namely: a danger of joining Ottoman Empire and Bulgaria to Central Powers
after entering into the war by Greece in the first months of the conflict, an
influence of Dardanelles operation on the positions of Greece and British
diplomacy, an activity of French foreign service. Methods of British diplomacy,
notably territorial compensations, financial assistance and bribery, were discovered. У статті розкрито британську політику щодо залучення Греції у
Першу світову війну на боці Антанти. Проаналізовано інтереси грецьких
політичних кіл та Foreign Office у взаємній співпраці, перебіг переговорів
про умови участі Греції у війні, вимоги, які висували сторони. Досліджено
чинники, які впливали на дипломатію Великої Британії, а саме: загрозу
приєднання до Центральних держав Османської імперії та Болгарії зі
вступом Греції у війну в перші місяці конфлікту, вплив Дарданелльської
операції на позицію грецької та британської дипломатії, діяльність
французького зовнішньополітичного відомства. Розкрито методи, якими
оперувала британська дипломатія, зокрема, територіальні компенсації, фінансова допомога та підкуп.